Economical multiple-site intradermal immunisation with human diploid-cell-strain vaccine is effective for post-exposure rabies prophylaxis. - Warrell, M; Nicholson, K; Warrell, D; Suntharasamai, P; Chanthavanich, P; Viravan, C; Sinhaseni, A; Chiewbambroongkiat, M; Pouradier-Duteil, X; Xueref, C (1985)
An economical post-exposure regimen of Mérieux human diploid-cell-strain vaccine (HDCSV) was compared with Semple vaccine (SV), the most widely used vaccine in Asia. 155 patients bitten by animals proved to be rabid received either conventional courses of SV (34 severe and 43 mild cases) or HDCSV, 0.1 ml intradermally, at eight sites on day 0, at four sites on day 7, and at one site on days 28 and 91 (36 severe and 42 mild cases). All severely bitten patients were given equine anti-rabies serum (EARS), 80 IU/kg on day 0. There were no deaths from rabies in either group. Follow-up was 97.5% at 1 year and 93% at 2 years. 88% of patients given HDCSV alone had detectable neutralising antibody on day 7 in contrast to 2% given SV alone. Antibody persisted until 1 year in all sera tested from HDCSV patients in contrast to only 48% of SV sera. The high dose of EARS resulted in pronounced suppression of response to HDCSV. There were no serious systemic side-effects but local side-effects were significantly more common in the SV group. The multiple-site intradermal HDCSV regimen was at least as effective as SV. The amount of HDCSV used was 30% of the conventional dose.